Postharvest Anthocyanin Enhancement in Blood Orange Fruit - Fariborz Habibi; Ali Sarkhosh; Jeffrey K. Brecht (EDIS)
This article discusses the postharvest enhancement and preservation of anthocyanin content in blood oranges grown in subtropical or tropical regions, such as Florida, for fresh consumption or for juice processing. The purpose of this article is to introduce growers, Extension agents, and specialists to simple postharvest methods for enhancing anthocyanin content in blood oranges, making the fruit more nutritious and more acceptable for consumption. Written by Fariborz Habibi, Ali Sarkhosh, and Jeffrey K. Brecht, and published by the UF/IFAS Department of Horticultural Sciences, June 2025.